Biomass co-firing to improve the burn-out of unreactive coals in pulverised fuel combustion - Bridge, Christopher P. (2018)
Biomass utilisation as a fuel in power generation has become an increasingly attractive prospect due to legislation and consumer awareness surrounding fossil fuels and their effect on climate change. However, a large portion of the world relies upon energy produced from readily available local coal sources. Large quantities of these local coals have low combustion efficiencies and energy outputs. An investigation was conducted to improve the combustion performance of these unreactive coals through the addition of small quantities of biomass in co-fired pulverised fuel conditions. To assess whether unreactive coal co-fired with biomass produced improved combustion performance a study of slow heating interactions was undertaken. Through the use of laboratory thermal conversion techniques, thermogravimetric analysis and horizontal tube furnace, slow heating ramp rates were achieved. Samples blended on a 50% coal loading experienced these conditions. Slow heating pyrolysis on a 50% coal loading displayed no synergistic improvement to VM content of coal blended with biomass, whilst catalytic increases of char reactivity were observed for coal blended with high ash biomass species through burn-out testing, such as OC. Following the baseline observations for slow heating conditions, blended samples were subjected to fast heating ramp rate conditions, through the use of a drop tube furnace. At fast heating pyrolysis conditions on a 50% coal loading synergistic improvements of VM yield were observed for coal blends with low ash biomass species, such as W. High ash biomass species showed minimal evidence of synergetic increase to VM, instead displaying the catalytic improvements to char burn-out performance, as seen with slow heating rates. A trail of varying coal loading ratios was conducted to determine the quantity of biomass required to observe the greatest improvements and to ascertain the viability of findings at industrially relevant conditions. Synergistic improvements in VM yield were caused by a steam gasification mechanism during fast heating ramp rates whilst catalytic improvements were caused by the presence of high quantities of alkali and alkaline earth metals (AAEMs). Fast heating rate coal blend trials conducted with partially demineralised biomass fuels provided a deeper understanding of the influence that AAEMs had on char reactivity. A regression analysis provided a quadratic model that demonstrated a strong relationship between AAEMs and char reactivity, with a correlation coefficient R2 value in excess of 95%. A fast heating rate combustion test was conducted to determine whether improvement to ignition distance could be achieved through co-firing. Both qualitative and semi-quantitative analysis of the captured particle images were inconclusive as to improvements in ignition distance.